Skeletal muscle effects of antisense oligonucleotides targeting glycogen synthase 1 in a mouse model of Pompe disease - Lan Weiss; Michele Carrer; Alyaa Shmara; Angela Martin; Hong Yin; Pallabi Pal; Cheng Cheng; Lac Ta; Victoria Boock; Yasamin Fazeli; Mindy Chang; Marvin Paguio; et al. (Clinical and Translational Medicine)
Abstract Pompe disease (PD) is a progressive myopathy caused by the aberrant accumulation of glycogen in skeletal and cardiac muscle resulting from the deficiency of the enzyme acid alpha‐glucosidase (GAA). Administration of recombinant human GAA as enzyme replacement therapy (ERT) works well in alleviating the cardiac manifestations of PD but loses sustained benefit in ameliorating the skeletal muscle pathology. The limited efficacy of ERT in skeletal muscle is partially attributable to its inability to curb the accumulation of new glycogen produced by the muscle enzyme glycogen synthase 1 (GYS1). Substrate reduction therapies aimed at knocking down GYS1 expression represent a promising avenue to improve Pompe myopathy. However, finding specific inhibitors for GYS1 is challenging given the presence of the highly homologous GYS2 in the liver. Antisense oligonucleotides (ASOs) are chemically modified oligomers that hybridise to their complementary target RNA to induce their degradation with exquisite specificity. In the present study, we show that ASO‐mediated Gys1 knockdown in the Gaa−/− mouse model of PD led to a robust reduction in glycogen accumulation in skeletal muscle. In addition, combining Gys1 ASO with ERT slightly further reduced glycogen content in muscle, eliminated autophagic buildup and lysosomal dysfunction, and improved motor function in Gaa−/− mice. Our results provide a strong foundation for validation of the use of Gys1 ASO, alone or in combination with ERT, as a therapy for PD. We propose that early administration of Gys1 ASO in combination with ERT may be the key to preventative treatment options in PD. Key points Antisense oligonucleotide (ASO) treatment in a mouse model of Pompe disease achieves robust knockdown of glycogen synthase (GYS1). ASO treatment reduces glycogen content in skeletal muscle. Combination of ASO and enzyme replacement therapy (ERT) further improves motor performance compared to ASO alone in a mouse model of Pompe disease.